First clinical report of aspiration through a novel 0.088-inch catheter positioned in the M1 middle cerebral artery for ELVO thrombectomy. Issue 10 (8th October 2020) - Gershon, Blake S; Bageac, Devin V; Shigematsu, Tomoyoshi; Majidi, Shahram; De Leacy, Reade
Abstract : Two patients, separated by 1 year, underwent mechanical thrombectomy using next generation, highly navigable 0.088-inch large bore catheters, which were navigated to and aspirated within the M1 middle cerebral artery segment. Case 1 demonstrates the first reported clinical application of this technique used in conjunction with stent retriever and direct aspiration through an intermediate catheter, resulting in modified thrombolysis in cerebral infarction (mTICI) score 3 recanalisation, and a 90-day modified Rankin Score of 1. In case 2, direct on-clot aspiration was applied through a 0.088-inch guide catheter in the left M1 segment, resulting in mTICI score 3 recanalisation and a National Institutes of Health Stroke Scale score of 1 at discharge. There was no evidence of untoward events in either case. Advancement of a 0.088-inch catheter into the M1 segment offers potential benefits to thrombectomy by improving device-thrombus interaction, inducing local flow arrest and protecting proximal vessels from embolus to new territories.